2019
DOI: 10.1155/2019/4681825
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nitrogen Fertilization Regimes for Sustainable Maize (Zea mays L.) Production on the Volcanic Soils of Buea Cameroon

Abstract: Nitrogen (N) fertilizer is commonly used to improve soil fertility and maize production in Cameroon, but high cost and potential environmental effects have necessitated site-specific N fertilization regimes that are adapted to particular soil and crop types. A field experiment was conducted with five N application rates (control–0, 50, 100, 150, and 200 kg N ha−1) to determine optimum rate for best maize yield with limited effect on soil acidification. The soil residual N ranged from 0.18 to 0.36% across N app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
6
20
0
Order By: Relevance
“…Nitrogen doses did not have any effects on the number of ears plant −1 as this is genetically controlled rather than by management factors. In line with our findings, Sharma et al [51] and Ngosong et al [52] also reported non-significant effects of N doses (0-240 kg ha −1 ) on the number of ears plant −1 . In our study, N doses above 120 kg ha −1 did not show any effects on most agronomic traits.…”
Section: Effect Of Nitrogen In Agronomic and Yield Attributing Traitssupporting
confidence: 92%
See 1 more Smart Citation
“…Nitrogen doses did not have any effects on the number of ears plant −1 as this is genetically controlled rather than by management factors. In line with our findings, Sharma et al [51] and Ngosong et al [52] also reported non-significant effects of N doses (0-240 kg ha −1 ) on the number of ears plant −1 . In our study, N doses above 120 kg ha −1 did not show any effects on most agronomic traits.…”
Section: Effect Of Nitrogen In Agronomic and Yield Attributing Traitssupporting
confidence: 92%
“…Beatty and Wong [26] also disseminated that reducing nutrient loss could simultaneously increase nutrient efficiency through the application of optimum dose; the minimum dose that produces maximum biomass and grain yield. In accord with our findings, several previous studies reported higher NUEs at lower N levels while evaluating improved and hybrids varieties of maize at 0-280 kg ha −1 N doses [52,58,[76][77][78]80,[82][83][84]. The range of yield increment kg −1 N application was 22.01-38.16 kg at N doses of 45-150 kg ha −1 [76,80,82,84].…”
Section: Nitrogen Uptake and Use Efficiencysupporting
confidence: 91%
“…The authors found similarly shorter cob length in treatments that received no nitrogen fertilization and longest cob length under higher N rate treatments. Ngosong et al [47] in their study, showed that different N rates had significant variation on maize cob length in the range of 14.5 to 18 cm as compared to the control, while [10] also reported that application of nitrogen generally promotes growth and yield components of maize and results in longer cob length.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that farmers use different types of inorganic fertilizer in order to improve soil fertility and increase crop yield (Jaza-Folefack, 2009;Chianu et al, 2012;Kamga et al, 2013;Asongwe et al, 2014;Tsozue et al, 2015;Tayoh et al, 2017;Mishra et al, 2018;Engwali et al, 2019;Ngosong et al, 2019;Depigny et al, 2019;Thuries et al, 2019;Tambi et al, 2019;Temegne et al, 2020;Buvaneshwari et al, 2020;Kelly and Naseem, 2020;Djoufack et al, 2020). However, few studies have tried to examine the types of inorganic fertilizer used by agroforestry and non-agroforestry practicing farmers which has been done in this study.…”
Section: Types Of Inorganic Fertilizer Used By Agroforestry and Non-amentioning
confidence: 99%